Housing during the asylum process and its association with healthcare utilization for common mental disorders among refugees in Sweden: A nationwide cohort study. - Charlotta van Eggermont Arwidson; Jessica Holmgren; Kristina Gottberg; Petter Tinghög (PLOS Global Public Health)
Refugees and asylum seekers face an increased risk of poor mental health, and evidence shows that housing in the post-migration context plays a crucial role in shaping their mental well-being. Research also suggests that institutional accommodations during the asylum process might be more detrimental to their mental health compared to private accommodations. We aimed to prospectively estimate the associations between housing type during the asylum process (institutional or self-organized accommodations) and healthcare utilization for common mental disorders (CMDs) after being granted a residence permit as a refugee in Sweden. This register-based cohort study includes all asylum seekers aged 18-60 who were granted residence permits in Sweden between 2010 and 2012, totaling 20,396 individuals, of whom 11,694 resided in self-organized housing (EBO) and 8,702 in accommodation centers (ABO). Using a generalized estimating equation (GEE), we estimated the associations between housing type (ABO or EBO) and prescriptions for antidepressants or anxiolytic medication, as well as specialized in- and outpatient visits with a diagnosis of CMDs, over a five-year follow-up period after being granted a residence permit. The adjusted odds ratio (controlled for sociodemographic factors) showed that those who had lived in ABO, compared with EBO, had a greater risk of any antidepressant or anxiolytic prescriptions (OR = 1.32, [1.21-1.44]) as well as any specialized in- or outpatient visits with a CMD diagnosis (OR = 1.41 [1.27-1.52]). Our results demonstrate that former asylum seekers who have lived in institutional housing use more mental healthcare services than those who have lived in self-organized housing, even when potential sociodemographic confounders and mediators are adjusted for. These associations persisted for up to five years after they had received a residence permit, highlighting that when asylum seekers live in institutional housing it is especially important to discuss how health can be promoted during the asylum-seeking period.